(untitled) (Journal of Geography and Environmental Management, 2019)
Growing population, lack of water resources, the massive amount of water withdrawal, and migration of people from rural to urban areas are creating a water scarcity issues in Pakistan. However, the suitable quantity of water resources is decreasing due to the unsustainable extraction of water resources whereas the land availability for the construction of domestic areas is reducing because of migration of people and urban areas are becoming overcrowded. Therefore, the aim of present work is to analyse the population distribution in the different province of Pakistan as well as the amount of total blue water, people access to drinking water and water withdrawal activities. To determine the outcomes/results the datasets have been downloaded from various sources i.e. SEDAC (NASA), World pop, Joint Research Centre (JRC-GHS), Gridded Population of the World version 4 (GPWv4) and aqueduct map 2.0. Population distribution and water resources maps have been investigated in the implementation of mapping algebraic approach in the context of Quantum Geographic Information system (QGIS). Classification, overlapping, clipping, masking and other GIS techniques are applied with the help of raster and vectors datasets. By using zonal statistics tool, we examined the number of people living in each province of Pakistan. However, through the overlapping of population density and water resources maps, we derived the outcomes that in which part of the country people are extracting the massive amount of water resources and where people are facing the water scarcity related issues.